The psychosocial impact of alopecia in men: A mixed‐methods survey study - Fabio Zucchelli; Abbi Mathews; Nick Sharratt; Kerry Montgomery; Jen Chambers (Wiley, 2024)
Abstract Background The most common forms of hair loss in men, alopecia areata (AA) (an autoimmune condition) and androgenetic alopecia (AGA) (pattern baldness), alter individuals' appearance in ways that may impact psychological and social wellbeing. We currently have a limited understanding about this impact of alopecia in men, their support needs, and preferences. Objectives We sought to investigate and explore the psychosocial impact of alopecia on men, alongside their experiences of treatment and support. Methods The study used a mixed methods cross‐sectional online survey with 177 men aged 17-79: 83 with AGA and 94 with AA. Quantitative questions included purpose‐made rating scales of men's support experiences, and standardised measures of wellbeing and appearance‐focused anxiety. Qualitative data comprised participants' answers to an open‐ended question asking about their subjectively salient experiences related to their alopecia. Results The combined findings indicate that while participants in both subsamples had sought minimal support for psychosocial concerns, such concerns were in fact commonplace. Over half of participants (56%-57%) shared qualitative accounts of depleted confidence, while wellbeing scores were on average lower than matched norms. Participants identifying as sexual minority also reported greater appearance‐focused anxiety compared to those identifying as straight. Conclusions The apparent contrast between participants' minimal help‐seeking and accounts of affected wellbeing suggests an unmet support need for men with alopecia. Masculine norms may impede men from accessing psychosocial support, both by discouraging help‐seeking behaviours and by encouraging minimisation of appearance concerns. The findings also suggest sexual minority status may pose a greater risk of distress in affected men.